Acceptability of an inactivated influenza vaccine delivered by microneedle patch: Results from a phase I clinical trial of safety, reactogenicity, and immunogenicity. Issue 45 (21st October 2020) - Frew, Paula M.; Paine, Michele Bennett; Rouphael, Nadine; Schamel, Jay; Chung, Yunmi; Mulligan, Mark J.; Prausnitz, Mark R.
Highlights: We evaluated acceptability of influenza vaccine by microneedle patch (MNP). Participants' attitudes about MNPs were influenced by experience MNP influenza vaccination information may influence people's vaccine acceptance. Most participants accepted influenza MNP vaccination compared to injection. MNP influenza vaccination may improve acceptability, safety, and logistics. Abstract: Objective: This study sought to evaluate the acceptability of inactivated influenza vaccine delivered by microneedle patch (MNP) in comparison to inactivated influenza vaccine (IIV) delivered by hypodermic needle. Design, Setting, and Participants. From the general population of Atlanta, Georgia, we screened 112 and enrolled 100 healthy adult subjects ages 18 to 49 years. Main Outcome(s) and Measure(s) . Our participants were randomized to 4 groups of 25 per arm: (1) IIV by MNP administered by healthcare worker (HCW), (2) IIV by MNP self-administered by study participants, (3) IIV by intramuscular (IM) injection administered by HCW or (4) placebo by MNP administered by HCW. We administered four questionnaires: at Day 0 before and after study product delivery, and at Days 8 and 28. Results: At baseline, 98.6% of participants receiving MNP vaccination reported an overall positive experience with MNPs, compared to 86.4% for participants receiving IM vaccination. For future influenza vaccination, study participants (N = 99) preferred MNP (n = 65, 69.9%) to injections or nasal spray (n = 20, 21.5%), and the preference for MNP increased from Day 0 to Day 28. Factor analyses resulted in two scaled measures including MNP Use Perceptions (a = 0.799, n = 5 items) and MNP Perceived Convenience (a = 0.844, n = 4 items) that were included in longitudinal assessments; while findings reflect significant differences across treatment groups on mean scores for ease of use, MNP perceived protection, MNP reliability, and MNP selection knowledge, all groups reported their belief that influenza vaccination by MNP would be reliable and protective, as well as easy-to-use and convenient. Conclusions and Relevance: Most participants were accepting of IIV vaccination by MNP and preferred it to injection. Delivery of IIV by MNP may help increase vaccination coverage.